2020
DOI: 10.1159/000506461
|View full text |Cite
|
Sign up to set email alerts
|

The Visceral Adiposity Index Is a Predictor of Incident Chronic Kidney Disease: A Population-Based Longitudinal Study

Abstract: Background and Aims: Visceral adiposity index (VAI), calculated with body mass index, high density lipoprotein-cholesterol, triglycerides and waist circumference, has been proposed as a marker of visceral fat accumulation and dysfunction in adipose tissue. Methods: The impact of VAI on incident chronic kidney disease (CKD) in a historical cohort study of 15,159 (8,260 men and 6,899 women) participants was investigated. CKD was defined when estimated glomerular filtration rate was < 60 mL/min/1.73 m 2 or protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…First, VAI is a representative marker to assess visceral adiposity which is strongly related with insulin resistance [ 34 ], and insulin resistance may lead to hypo-inflammation [ 35 ], endothelium dysfunction [ 36 ], and oxidative stress [ 37 ], contributing to the development of microangiopathy. Podocytes are insulin sensitive renal cells, and thus the insulin resistance is more likely to cause kidney damage [ 38 ]. Second, VAI is a valuable indicator of visceral adipose function [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, VAI is a representative marker to assess visceral adiposity which is strongly related with insulin resistance [ 34 ], and insulin resistance may lead to hypo-inflammation [ 35 ], endothelium dysfunction [ 36 ], and oxidative stress [ 37 ], contributing to the development of microangiopathy. Podocytes are insulin sensitive renal cells, and thus the insulin resistance is more likely to cause kidney damage [ 38 ]. Second, VAI is a valuable indicator of visceral adipose function [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the median follow-up period of 2.46 years, the occurrence rate of incident CKD in our study was 16.68% ( n = 931). Another longitudinal study conducted by Bamba et al ( 16 ) enrolled 15,159 general population without baseline medication or CKD. During the median 3.3-year follow-up for men and 3.2-year follow-up for women, the occurrence rate of incident CKD in their cohort was 7.62% and 6.51%, respectively ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another longitudinal study conducted by Bamba et al ( 16 ) enrolled 15,159 general population without baseline medication or CKD. During the median 3.3-year follow-up for men and 3.2-year follow-up for women, the occurrence rate of incident CKD in their cohort was 7.62% and 6.51%, respectively ( 16 ). Comparing with the previous result, the occurrence rate of incident CKD in our cohort was higher.…”
Section: Discussionmentioning
confidence: 99%
“…These effects can then result in the ectopic accumulation of lipids and increases in renal sinus fat, glomerular hypertension, and increased permeability of the glomeruli through glomerular filtration barrier injury related to hyperfiltration, and consequently glomerulomegaly and focal or segmental glomerulosclerosis [44,45]. This mechanism could also explain that the higher VAI was associated with incident CKD, and many previous studies had also proved the same result [46,47]. In previous meta-analyses and systemic reviews, WHtR was shown to have the best discriminatory ability for the risk of hypertension, diabetes, and dyslipidemia [48,49].…”
Section: Discussionmentioning
confidence: 86%